2000
DOI: 10.1074/jbc.275.12.9047
|View full text |Cite
|
Sign up to set email alerts
|

The c-Jun NH2-terminal Kinase Promotes Insulin Resistance during Association with Insulin Receptor Substrate-1 and Phosphorylation of Ser307

Abstract: Tumor necrosis factor ␣ (TNF␣) inhibits insulin action, in part, through serine phosphorylation of IRS proteins; however, the phosphorylation sites that mediate the inhibition are unknown. TNF␣ promotes multipotential signal transduction cascades, including the activation of the Jun NH 2 -terminal kinase (JNK). Endogenous JNK associates with IRS-1 in Chinese hamster ovary cells. Anisomycin, a strong activator of JNK in these cells, stimulates the activity of JNK bound to IRS-1 and inhibits the insulin-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
994
5
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,284 publications
(1,079 citation statements)
references
References 65 publications
47
994
5
11
Order By: Relevance
“…Mounting evidence indicates that activation of c-Jun N-terminal kinase (JNK), IKK and conventional PKC is central to the development of insulin resistance in response to obesity -mediated by the aforementioned fatty acidinduced ER stress, ROS production, TLR activation and inflammatory signalling by TNF . JNK, IKK and PKC have all been reported to inhibit insulin action by phosphorylating IRS1 on serine [80][81][82] . Serine phosphorylation of IRS1 disrupts insulin-receptor signalling through several distinct mechanisms and blocks insulin action 83,84 .…”
Section: Nature Reviews | Molecular Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence indicates that activation of c-Jun N-terminal kinase (JNK), IKK and conventional PKC is central to the development of insulin resistance in response to obesity -mediated by the aforementioned fatty acidinduced ER stress, ROS production, TLR activation and inflammatory signalling by TNF . JNK, IKK and PKC have all been reported to inhibit insulin action by phosphorylating IRS1 on serine [80][81][82] . Serine phosphorylation of IRS1 disrupts insulin-receptor signalling through several distinct mechanisms and blocks insulin action 83,84 .…”
Section: Nature Reviews | Molecular Cell Biologymentioning
confidence: 99%
“…JNK is activated after exposure to cytokines, such as TNF , as well as by free fatty acids through the TLR pathway and internal cues such as ER stress, all of which might underlie its obesity-induced activity 60,80,85 . There is a striking increase in JNK activity at crucial metabolic sites such as adipose and liver tissue in mouse models of obesity 86 .…”
Section: Nature Reviews | Molecular Cell Biologymentioning
confidence: 99%
“…Over the ensuing 24 h, JNK phosphorylation levels decrease concomitantly with a rise in Akt phosphorylation [11,31]. Since JNK is known to suppress insulin signalling [32], it is possible that the insulin signalling pathway is suppressed in islets immediately following isolation and Akt only becomes activated following suppression of the JNK pathway. We therefore examined whether exogenous insulin could induce Akt phosphorylation in islets immediately following isolation, at a time when JNK is highly activated.…”
Section: Regular Medium Replacement Decreases Akt Phosphorylationmentioning
confidence: 99%
“…In type 1 diabetes, JNK plays a central role in the intracellular events that signal beta cell loss after exposure to the proinflammatory cytokine IL-1β [24,25]. JNK is abnormally elevated in various tissues under diabetic conditions due to the phenomenon known as glucose toxicity, and it has been demonstrated that activation of the JNK pathway interferes with insulin action [26][27][28] and beta cell function [29,30], as well as with insulin biosynthesis [29]. Islet transplantation involves the exposure of islets to several forms of stress, not only as a result of pancreas preservation and islet isolation, but also of inflammation and glucose toxicity after transplantation.…”
Section: Introductionmentioning
confidence: 99%